Jesus Cristo é o senhor: há contribuições da Igreja Universal do Reino de Deus à Igreja Batista? - Fernandes, Wilson (2010)
This work intends to study the so-called neo-Pentecostal religious phenomenon, specifically the Igreja Universal do Reino de Deus. The delimitacional cut falls within the Protestant religious reality of Brazil, It aims to search bibliographically the phenomenon of Brazilian neo-Pentecostal growth and social circumstances in which it occurs. We seek to understand the process of expansion and acceptance of their proposals to the population by the population. As a result, the research expected to raise positive points or perceptions that may be indicators which are contributing to the churches considered historical. The study was accomplished based on a neopentecostal referral, here in case the Igreja Universal do Reino de Deus, and a historic Baptist Church, specifically the Convenção Batista Brasileira.